Adherence to the World Cancer Research Fund/American Institute for Cancer Research cancer prevention recommendations and breast cancer risk in the Cancer de Màma (CAMA) study. Issue 18 (25th March 2015) - Fanidi, Anouar; Ferrari, Pietro; Biessy, Carine; Ortega, Carolina; Angeles-Llerenas, Angélica; Torres-Mejia, Gabriella; Romieu, Isabelle
Abstract: Objective: We investigated the association between adherence to the recommendations of the World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) and breast cancer (BC) risk in the Cancer de Màma (CAMA) study in a Mexican population. Design: Population-based case–control study. Subjects: Incident BC cases ( n 1000) and controls ( n 1074) matched on age, region and health-care system were recruited. Setting: In-person interviews were conducted to assess BC risk factors and habitual diet was assessed with an FFQ. Conformity to the WCRF/AICR recommendations was evaluated through a score incorporating seven WCRF/AICR components (body fatness, physical activity, foods and drinks that promote weight gain, plant foods, animal foods, alcoholic drinks and breast-feeding), with high scores indicating adherence to the WCRF/AICR recommendations. Results: No statistically significant associations between WCRF/AICR score and risk of BC were observed. After excluding BMI from the WCRF/AICR score, the top quartile was associated with a decreased BC risk overall, with ORQ4–Q1 =0·68 (95 % CI 0·49, 0·92, P trend =0·03), and among postmenopausal women, with ORQ4–Q1 =0·60 (95 % CI 0·39, 0·94, P trend =0·03). Inverse associations were observed between BMI and risk of BC overall and among premenopausal women, with OR=0·57 (95 % CI 0·42, 0·76, P trend <0·01) and 0·48 (95 % CI 0·31, 0·73, P trend <0·01), respectively. Physical activity level was inversely associated with BC risk. Conclusions: The WCRF/AICR index was not related with BC risk in the CAMA study. A combination of six components excluding BMI showed strong protective associations, particularly in postmenopausal women. Further prospective studies are required to clarify the role of adherence to WCRF/AICR recommendations, particularly with respect to BMI, in the Mexican population.